Selfies in Auschwitz: Popular and contested representations in a digital generation. (April 2023) - Feldman, Jackie; Musih, Norma
Selfies at Auschwitz have become increasingly popular, and have generated agitated public debate. While some see them as an engaged form of witnessing, others denounce them as a narcissistic desecration of the dead. We analyze the taking, composition, and circulation of several of the most popular selfies of Auschwitz and the online reactions to them. The practice of selfies marks a shift from witness to witnessee and from onsite to online presence. Yet it also builds on previous practices: photography, postcards and souvenirs, the affordances of the architecture of the memorial site, the bodily presence of the survivor-witness as mediator of the Holocaust, and the redemptive value assigned to the physical presence of the visitor as "witness of the witness." We suggest that the combination of continuities with the past alongside the radical break with previous witnessing practices empowers selfie-takers, while arousing the indignation of gatekeepers of Holocaust memory.